Evaluation of Dietary Inorganic and Organic Selenium Sources on Immune Organ, Plasma Immunoglobulins, Blood Biochemical, and Performance of Broilers: A Meta-Analysis - Wijayanti, I.; Risyahadi, S. T.; Sukria, H. A.; Retnani, Y.; Jayanegara, A.; Kusuma, R. I.; Daulai, M. S.; Hasanah, Q. N. (Tropical Animal Science Journal, 2023)
The current meta-analysis aimed to estimate the effect of different selenium (Se) sources on immune organs, plasma immunoglobulins, blood profiles, and broiler performances. Related studies that met standard presence criteria were identified and mined from the Scopus database. The database was developed from 38 articles. Data were analyzed using the OpenMEE, considering the difference between organic selenium as fixed effects and different studies as random effects. This study showed that organic selenium feed supplementation improved the feed conversion ratio and increased the average daily feed intake and gain of broilers. Furthermore, the mortality of broilers fed organic Se was significantly lower than that of those fed inorganic Se. For the immune organ of the broiler, organic selenium feed supplement enhanced the thymus and spleen organs but did not affect the bursa organ. IgA and IgM were significantly higher in the broilers fed organic selenium feed; meanwhile, IgG of broilers fed organic selenium was lower than those fed inorganic selenium. The total protein blood concentration of broilers fed organic selenium was significantly higher than those fed inorganic Se. Meanwhile, there was no statistically significant difference in the effects of selenium source on cholesterol. Triglyceride concentrations of broilers fed organic Se are significantly lower than those fed inorganic Se. The ratio of heterophile to lymphocyte in broilers fed organic Se is significantly lower than in those fed inorganic selenium. In conclusion, the organic selenium feed supplement can promote production performance and immune parameters of broilers.